The Effect of Depressive Symptoms and CD4 Count on Adherence to Highly Active Antiretroviral Therapy in Sub-Saharan Africa. (July 2014) - Memiah, Peter; Shumba, Constance; Etienne-Mesubi, Martine; Agbor, Solomon; Hossain, Mian B.; Komba, Patience; Niyang, Mercy; Biadgilign, Sibhatu
Background: Studies have identified several programmatic and nonprogrammatic indicators that affect adherence to highly active antiretroviral therapy (HAART). Depression has been shown to impact adherence to HAART. This cross-sectional analysis of data collected from Nigeria, Uganda, Zambia, and Tanzania in 2008 examined the relationship between levels of depressive symptoms, clinical progression, and adherence to HAART. Methods: A multinational, multicenter, observational, retrospective cross-sectional evaluation of a population of focus comprised randomly selected patients on HAART. The dependent variable was adherence to HAART. The primary variable of interest to be assessed was patients' level of depressive symptom score. A multivariable logistic regression model was used to examine the relationship between explanatory variables and adherence to HAART. Results: A total of 2344 patients were recruited for adherence survey. About 70% of the study sample reported having some level of depression. Logistic regression results show that patients who reported, respectively, low, moderate, and high levels of depressive symptoms are 35% ( P < .001), 56% ( P < .001), and 64% ( P < .001) less likely to adhere to HAART than those who reported having no depressive symptoms. At multivariate analysis, adherence to HAART was independently associated with the levels of depressive symptoms, older age, CD4 count >200 cells/mm 3, Truvada (tenofovir [TDF]/emtricitabine [FTC])-based regimens, good knowledge about HAART, and longer period on therapy. Conclusions: These results indicate that mental health and clinical parameters are significant factors in determining patients' adherence to their HAART, which need to be more aggressively addressed as a critical component of care and treatment support.